Pengertian, Fungsi dan Tujuan Manajemen Pendidikan - Istikhori Istikhori; Alfian Khadafi; Vikri Dwiki; Yuyu Yuhaeni (JURNAL RISET MANAJEMEN (JURMA), 2024)
Management is a key role in the educational world, along with independent science discipline, it also collaborates with education (bound). Increasingly, education begins to erode the characteristics of anomalies and destructions makes education lose its power, the education formulated to reflect less and less rivals by other powerful entities, supposedly this weakness rooted in fragile and fragile education management. This study will discuss how the management of education would tackle the problem, starting with its definition of a function of the management of education itself. As for the research methods used in this study are qualitative research methods, to be exact library research. With a documentary data collection technique and data analysis analysis of content analysis. The results of this study indicate that 1) the management of education is defined by a tool in the educational education done through planning, organizing activities. Education function, 2) a) planning (planning), b) organization (organization), c) staffing (organization), d) management (direction), e) coordination (coordination) g) reporting (reporting), h) budgeting (budgeting), while 3) the purpose of management is for the systematic and evaluative implementation of a endeavor.